2014
DOI: 10.1007/s00464-014-3607-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic treatment of incisional and primary ventral hernia in morbidly obese patients with a BMI over 35

Abstract: This study confirms the feasibility and safety of the laparoscopic approach for ventral hernias in morbidly obese patients. Recurrence rates (3.8%) appeared lower than the ones observed in the literature (15-25%). Postoperative hemorrhage and port-site hernia are specific complications of this approach. Postoperative hospital stay is low (2 days) as compared to open surgery. Laparoscopic management of parietal wall defects should be considered a standard option in morbidly obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Several studies have demonstrated the advantages of LVHR, even more so when addressed at the time of laparoscopic WLS, such as a roux-en-Ygastric bypass (RYGB). [11][12][13] These studies report a wide range of recurrence rates. Patients with a mean BMI of over 40 kg/m 2 who undergo laparoscopic repair had a recurrence rate ranging from 4% to 18%.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the advantages of LVHR, even more so when addressed at the time of laparoscopic WLS, such as a roux-en-Ygastric bypass (RYGB). [11][12][13] These studies report a wide range of recurrence rates. Patients with a mean BMI of over 40 kg/m 2 who undergo laparoscopic repair had a recurrence rate ranging from 4% to 18%.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic repair of large parietal wall defects is a wellaccepted and safe option for class II and class III obesity patients. 2 There are many parameters adherent to hernias (size, location, primary versus recurrent, symptomatic versus asymptomatic, reduced versus nonreduced) that may affect the decision to perform a ventral hernia repair during a bariatric procedure. In a 2017 large cohort study there was increased 30 day morbidity, 3 although specific hernia characteristics were not assesed.…”
Section: Discussionmentioning
confidence: 99%
“…[40] Laparoscopic AWR seems also to be associated with fewer surgical site infections and reoperations [8] and with a shorter hospital stay. [9] Nevertheless, in morbidly obese patients, a staged or concomitant bariatric surgery has been shown to be safe and feasible.…”
Section: Discussionmentioning
confidence: 99%